PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS ANIMASI PADA KELISTRIKAN BODI KENDARAAN - Mohamad Eko W. Ismail; Muhammad Yasser Arafat; Hendra Uloli (Steam Engineering, 2023)
The purpose of this study is to develop and determine the feasibility of animation-based interactive learning media on the vehicle body electrical system. The research method used is Research and Development (R&D) using the Four D (4D) Define, Design, Development, and Dissemination model. The data analysis technique used is quantitative and qualitative analysis techniques. The location of this research is at Gorontalo State University and the research subjects are students who have completed or are currently taking Automotive Electrical courses. The data collection technique is a questionnaire to test the feasibility of the media. The results of this study produced a product in the form of interactive learning media based on animation on the body's electrical system. The designed learning media is declared valid because it has been tested for its validity by media experts at 81.7%, material experts at 86.6%, and students at 90%. Based on the data above, it can be concluded that the media developed is very feasible and can be used as a learning tool in the Mechanical Engineering Education Study Program, State University of Gorontalo.